2022
DOI: 10.5194/egusphere-2022-1043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Volatility of aerosol particles from NO3 oxidation of various biogenic organic precursors

Abstract: Abstract. Secondary organic aerosol (SOA) is formed through the oxidation of volatile organic compounds (VOC), which can be of both natural and anthropogenic origin. While the hydroxyl radical (OH) and ozone (O3) are the main atmospheric oxidants during the day, the nitrate radical (NO3) becomes more important during the night time. Yet, atmospheric nitrate chemistry has received less attention compared to OH and O3. The Nitrate Aerosol and Volatility Experiment (NArVE) aimed to study the NO3-induced SOA forma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 40 publications
(69 reference statements)
1
29
0
Order By: Relevance
“…The volatility distribution of pON from the SIMPOL‐acid group method shows similar patterns as that from the TD method (UC = 0.67–0.83), which exhibits more OA masses at two ends (log C* = −9 and log C* ≥ 2) (Figures 6c and 6d). This pattern suggests that both large fractions of oligomers with low volatilities and semi‐volatile species exist in pON, which is consistent with the volatility of pON generated from the laboratory studies (Graham et al., 2022), signifying the complexity of pON species. The volatility of pON was contributed by 74% CHON and 26% CHONS groups (Figure 6d), respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The volatility distribution of pON from the SIMPOL‐acid group method shows similar patterns as that from the TD method (UC = 0.67–0.83), which exhibits more OA masses at two ends (log C* = −9 and log C* ≥ 2) (Figures 6c and 6d). This pattern suggests that both large fractions of oligomers with low volatilities and semi‐volatile species exist in pON, which is consistent with the volatility of pON generated from the laboratory studies (Graham et al., 2022), signifying the complexity of pON species. The volatility of pON was contributed by 74% CHON and 26% CHONS groups (Figure 6d), respectively.…”
Section: Resultssupporting
confidence: 83%
“…Only limited laboratory studies have compared OA volatility among different technique categories. The comparability of OA volatility (a) between the dilution method and heating technique from TD‐AMS (Sato et al., 2019); (b) between dilution and FIGAERO‐CIMS (Graham et al., 2022; Tikkanen et al., 2020); (c) between FIGAERO‐CIMS versus TD‐AMS measurements (Voliotis et al., 2022; Voliotis et al., 2021); (d) between element‐versus functional groups‐based method (Isaacman‐VanWertz & Aumont, 2021; Wu et al., 2021), have varied under different circumstances, highlighting the necessity for further exploration on the factors causes this discrepancy. The intercomparison of volatility distributions for ambient OA among different methods is even scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, these concentrations can also result from thermal decomposition of lower volatility products during the FIGAERO-I-CIMS heating process (Lopez-Hilfiker et al, 2015) or from the tendency of the Eq. ( 18) parameterization to underestimate (despite treating the -NO3 groups at -OH groups) the volatility of organic nitrates (Graham et al, 2022), shown to be abundant in the BAECC FIGAERO-I-CIMS data set (Fig. 2e).…”
Section: Volatility Distributions Based On Figaero-i-cims Measurement...mentioning
confidence: 98%
“…Chemical composition and volatility of atmospheric organic aerosol (OA) particles are interconnected. Functionalization of organic molecules can modify their vapor pressure by several orders of magnitude (Pankow and Asher, 2008;Donahue et al, 2011;Graham et al, 2023;Isaacman-VanWertz and Aumont, 2021;Kroll and Seinfeld, 2008). Volatility determines whether a compound partitions into or evaporates from the particle phase and thus influences particulate mass and lifetime in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…1. The molecular information of OOA can be used to parametrize volatility via calculations of the effective saturation mass concentrations (C sat ) of different organic compounds (Donahue et al, 2011;Li et al, 2016;Mohr et al, 2019;Isaacman-VanWertz and Aumont, 2021;Graham et al, 2023). There are various parametrization methods to calculate C sat , based on different assumptions, training datasets, or structurebased estimation methods (Isaacman-VanWertz and Aumont, 2021).…”
Section: Introductionmentioning
confidence: 99%